Sintesis dan Karakterisasi Struktur Kristal Ion [Cr3O(OOCC6H5)6(H2O)3]4[Î±-SiW12O40]â 10H2Oâ 8CH3COCH3 - Aldes Lesbani (Institut Teknologi Bandung, 2008)
The complexation of polyoxometalate K4[Î±-SiW12O40] and organometallic complex of [Cr3O(OOCC6H5)6(H2O)3](NO3)forms ionic crystal of [Cr3O(OOCC6H5)6(H2O)3]4[Î±-SiW12O40]â 10H2Oâ 8CH3COCH3 (1a). Single crystal XRD analysisshowed that benzoic groups of organometallic complex were stacked to form eight-membered ring. The Ï-Ï interactionmay stabilize the crystal structure of 1a. FT-IR spectrum of ionic crystal showed that characteristic vibration ofpolyoxometalate and organometallic compound existed in the crystal. The amount of water molecules in 1a wasdetermined by using TG-DTA analysis. Ten water molecules were found in the ionic crystal of 1a. The GC analysisshowed that eight acetone molecules existed in the ionic crystal of 1a.